Waste disposal and its problems (Eurasian Journal of Ecology, 2016)
Questions on industrial waste. Utilization of and consumption of Aktuyubinskaya oblast. reduction of negative effect of waste on the people’s health and environment and waste recycling as alternative source ofenergy and materials are investigated in this article.
Keywords: recycling; manufacturing; waste; raw materials